2016
DOI: 10.1542/peds.2015-3387
|View full text |Cite
|
Sign up to set email alerts
|

Interventions To Prevent Retinopathy of Prematurity: A Meta-analysis

Abstract: CONTEXT: The effectiveness of many interventions aimed at reducing the risk of retinopathy has not been well established. OBJECTIVE:To estimate the effectiveness of nutritional interventions, oxygen saturation targeting, blood transfusion management, and infection prevention on the incidence of retinopathy of prematurity (ROP). DATA SOURCES:A comprehensive search of several databases was conducted, including Medline, Embase, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 98 publications
1
63
2
4
Order By: Relevance
“…Genetic and environmental factors are likely to play a role in the degree and duration of hyperoxia necessary to trigger the process, the resultant surge in vascular growth factors and the severity of disease that develops. Balancing oxygen supplementation is key: lower supplementation (85%–89% vs 91%–95%) reduces the risk of sight threatening ROP (risk ratio (RR) of 0.72, 95% CI 0.51 to 1.00) but increases the risk of mortality (RR 1.17, 95% CI 1.03 to 1.32) 38. The role of nutrition, haemoglobin transfusion or erythropoietin (EPO) administration is unclear, though meta-analysis of RCTS of early nutritional supplementation indicates a protective effect (RR 0.22, 95% CI 0.09 to 0.55 and RR 0.67, 95% CI 0.46 to 0.97, respectively) 36 38…”
Section: Retinopathy Of Prematuritymentioning
confidence: 99%
“…Genetic and environmental factors are likely to play a role in the degree and duration of hyperoxia necessary to trigger the process, the resultant surge in vascular growth factors and the severity of disease that develops. Balancing oxygen supplementation is key: lower supplementation (85%–89% vs 91%–95%) reduces the risk of sight threatening ROP (risk ratio (RR) of 0.72, 95% CI 0.51 to 1.00) but increases the risk of mortality (RR 1.17, 95% CI 1.03 to 1.32) 38. The role of nutrition, haemoglobin transfusion or erythropoietin (EPO) administration is unclear, though meta-analysis of RCTS of early nutritional supplementation indicates a protective effect (RR 0.22, 95% CI 0.09 to 0.55 and RR 0.67, 95% CI 0.46 to 0.97, respectively) 36 38…”
Section: Retinopathy Of Prematuritymentioning
confidence: 99%
“…However, a meta-analysis concluded that despite the fact that low oxygen concentration has been detected to decline the risk of ROP, it actually increases mortality (RR 1.15, 95% CI, 1.04-1.29) [76].…”
Section: Retinopathy Of Prematurity (Rop)mentioning
confidence: 99%
“…There is a growing body of evidence that no single therapy has proven to be effective and safe in preventing and treating ROP [73,76]. Managing ROP effectively necessitates coordination between physicians from different disciplines, such as neonatologists, obstetricians, and ophthalmologists.…”
Section: Retinopathy Of Prematurity (Rop)mentioning
confidence: 99%
“…Three recent meta-analyses show that any amount of human milk is strongly associated with ROP protection 2–4. One of them demonstrated a significant 60% reduction in severe ROP with increased human milk exposure, while lower oxygen saturation targets were associated with only a 42% reduced risk of severe ROP3; these findings hint that the effectiveness of interventions on oxygen concentrations aimed at reducing the risk of ROP has been over-rated, while the responsibility of formula feeding on ROP pathogenesis has been under-rated.…”
mentioning
confidence: 94%